2013
DOI: 10.1103/physreve.88.013103
|View full text |Cite
|
Sign up to set email alerts
|

Particle transport and radiation production in sub-Larmor-scale electromagnetic turbulence

Abstract: The relation of particle transport of relativistic particles in plasmas with high-amplitude isotropic sub-Larmor-scale magnetic turbulence to the spectra of radiation simultaneously produced by these particles is investigated both analytically and numerically. We have found that in the asymptotic regime of very small particle deflections, the pitch-angle diffusion coefficient is directly related to the spectrum of the emitted radiation. Moreover, this spectrum provides much information about the statistical pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(44 citation statements)
references
References 30 publications
3
40
1
Order By: Relevance
“…Additionally, we anticipated that an interconnection between the transport and radiative properties of electrons moving through small-scale Whistler turbulence exists, as it does for strictly Weibel-like, mean-field-free turbulence (Keenan & Medvedev 2013;Keenan et al 2015).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, we anticipated that an interconnection between the transport and radiative properties of electrons moving through small-scale Whistler turbulence exists, as it does for strictly Weibel-like, mean-field-free turbulence (Keenan & Medvedev 2013;Keenan et al 2015).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In our previous works (Keenan & Medvedev 2013;Keenan et al 2015), we showed that the pitchangle diffusion coefficient and the simultaneously produced radiation spectrum are wholly determined by the particle velocity and the statistical/spectral properties of small-scale (mean free) magnetic turbulence. Here, we have generalized these results to the case when the magnetic field has a mean value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,[31][32][33][34][35] We will show that the direct observation of mildly relativistic Weibler radiation may be feasible in the laboratory setting. We will focus our attention upon the experiment discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%